Commentary: A glass half full or half empty? Cognitive bias modification for mental health problems in children and adolescents – reflections on the meta‐analysis by Cristea et al. (2015). (July 2015) - Lau, Jennifer Y. F.
<x xml:space="preserve">Abstract</x> The last decade has cognitive bias modification (CBM) training paradigms, emerging first as an experimental test of the causal role of information‐processing biases on mood and anxiety symptoms, and then, as the clinical implications of these findings were realised, as a potential clinical 'vaccine' that could be used to modify biases and reduce symptoms. CBM is an umbrella term for methods designed to modify cognitive factors that maintain psychiatric conditions such as anxiety and depression through simple repetitive learning. Two biases that have most often been targeted by these training programs are the tendency to orient attention towards threat and distortions in the interpretation of ambiguous situations. This commentary reflects on an accompanying meta‐analysis by Crsitea et al., which pooled effect sizes from over 20 statistical comparisons between a CBM group and a control group on post‐training measures of mental health (mostly anxiety and depression). Cristea et al. reported that any CBM training‐associated difference on measures of anxiety and depression were weak and non‐significant (although training effects were generally evident on measures of cognitive biases). Heterogeneity across studies was high, but with exception to the setting in which CBM was delivered (home, school, laboratory or mental health facility), there was no persuasive evidence for significant moderation of training effects by other key variables. In their conclusions the authors suggested that CBM had little clinical utility and that it was unclear whether positive results in any individual study arose from experimenter or participant bias. So if the glass is half empty, what should the next stage of CBM research usefully focus on?